Implementation of Secret Key Generation on Mobile Crowdsensing Application to Secure Tracking Location of Motorcyclists - Dewi, Ni Made Lintang Asvini; Sudarsono, Amang; Yuliana, Mike (The Indonesian Journal of Computer Science, 2023)
Mobile crowdsensing is a method for collecting many data from sensors on smartphone. In this research, mobile crowdsensing application will be developed to display location of motorcyclits who connected in an Ad-Hoc network along with a security system using the Secret Key Generation (SKG) scheme to generate a secret key that will be used to encrypt and decrypt the data. From the results it can be concluded that the highest measurement correlation is 0.0398 and the lowest is 0.0018 but after randomness extraction proccess, the highest correlation is 0.996 and the lowest is 0.978. After encryption, information of Alice and Bob is stored as random character in database and decrypted as plaintext as shown as in application. In the attacking result, the data after encrypted just shown random character in traffic monitor. When the eavesdroppers manipulate its IP address like Alice's, they can’t connect to Bob.